Patient Costs and Physicians' Information - Dickstein, Michael J.,Jeon, Jihye,Morales, Eduardo (National Bureau of Economic Research, 2024)
Health insurance plans in the U.S. increasingly use price mechanisms to steer demand for prescription drugs. The effectiveness of these incentives, however, depends both on physicians' price sensitivity and their knowledge of patient prices. We develop a moment inequality model that allows researchers to identify agents' preferences without fully specifying their information. Applying this model to diabetes care, we find that physicians lack detailed price information and are more price-elastic than full-information models imply. We predict that providing physicians detailed information on prices at the point of prescribing can save patients 12-23% of their out-of-pocket costs for diabetes treatment
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Private Krankenversicherung; Gesundheitskosten; Arzneimittel; Diabetes; Preismanagement; Preiselastizität; Ärzte; USA; Analysis of Health Care Markets; Health Insurance; Public and Private; General; Information and Product Quality; Standardization and Compatibility